Analysis of Arabic Language Textbooks for Madrasah Aliyah Class XI Based on the 2013 Curriculum | Analisis Buku Ajar Bahasa Arab Madrasah Aliyah Kelas XI Berdasarkan Kurikulum 2013 - Laila Faoziyah; Nailul Izzah (Mantiqu Tayr: Journal of Arabic Language, 2021)
The issue raised in this research is about the material content of the Arabic language textbook Madarasah Aliyah Class XI published by the Ministry of Religion. This study aims to analyze the Arabic language textbooks for Madrasah Aliyah Class XI based on the 2013 curriculum. This research is a qualitative research with a literature study method. Data collection is done by documentation technique and data analysis that the writer uses is content analysis. While the 2013 Curriculum is a theory that is used as a medium to analyze qira'ah about Amal al-Murahiqin. The results of the study indicate that the Islamic Madarasah Aliyah Class XI Arabic Textbook published by the Ministry of Religion is in accordance with the 2013 curriculum. This can be seen from the material and pictures contained in it are in accordance with core competencies and basic competencies. In addition, the qira'ah material on Amal al-Murahiqin has included the values ​​of spiritual attitudes, social attitudes, knowledge, and skills taught in learning.